2021
DOI: 10.1002/cncr.33660
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance imaging during first remission in follicular lymphoma does not impact overall survival

Abstract: Background Although many patients with follicular lymphoma (FL) undergo routine radiographic surveillance during their first remission, no consensus exists on the modality, duration, frequency, or need for routine imaging studies. The authors retrospectively examined the effect of surveillance imaging on relapse detection and overall survival (OS) in patients with FL. Methods Patients with newly diagnosed FL who had a response to induction therapy were identified from the Lymphoid Malignancies Enterprise Archi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
(111 reference statements)
1
4
0
Order By: Relevance
“…Goldman et al 20 reported that surveillance imaging did not contribute to survival improvement in patients with FL; this was consistent with our study for both groups. OS is the most relevant endpoint; however, it has become more challenging to use OS for FL patients as an endpoint because of its long-term clinical course and treatment improvement.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Goldman et al 20 reported that surveillance imaging did not contribute to survival improvement in patients with FL; this was consistent with our study for both groups. OS is the most relevant endpoint; however, it has become more challenging to use OS for FL patients as an endpoint because of its long-term clinical course and treatment improvement.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the interval at which the surveillance CT was performed was not regular. In another study by Goldman et al, 20 18/55 (33%) patients in a retrospective cohort and 50/117 (43%) in a prospective validation cohort had asymptomatic imaging-detected relapses, and there was no significant difference in the OS between patients with surveillance imagingdetected relapse and clinically detected relapse. However, in their study, surveillance imaging methods were not defined, and they used CT or PET.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This additional prognostication resource provides the treating physician with a tool to add further precision concerning therapy decision, i.e., for early intensification or maybe also change of the therapeutic goals. However, while several therapies are very imaging-dependent these days, i.e., several types of lymphoma therapies are heavily PET/CT driven, this is not a universal finding [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study of 116 DLBCL patients, PET/CT showed a limited role in disease surveillance for patients achieving complete remission after primary therapy (Cheah et al 2013). For FL, a retrospective study examined the effect of surveillance imaging on relapse detection and OS and suggested that no OS benefit was associated with imaging-detected relapse (Goldman et al 2021). Owing to the lack of sufficient evidence demonstrating an improved outcome for the detection of relapse, the latest NCCN Guidelines do not recommend 18 F-FDG PET as routine surveillance for patients with stage I-II disease who have achieved complete metabolic response after the initial therapy (NCCN Clinical Practice Guidelines in Oncology 2021).…”
Section: F-fdg Pet/ct In Post-treatment Surveillance Of Lymphomasmentioning
confidence: 99%